The role of leadership qualities of the management in preserving and ensuring the functionality of relocated Ukrainian higher education institutions during the war - Kristina Petryk; Tetiana Mukhina; Karyna Koval; Nadiia Vientseva; Anzhelika Lesyk; Olha Popova; Tetiana Fatianova (Problems and Perspectives in Management)
The war in Ukraine has led to significant changes in the functioning of higher education institutions. Many universities from the eastern and southern regions of the country were forced to relocate to safer areas. The study examines the role of leadership qualities of the management of Ukrainian HEIs relocated due to the war on their success in functioning in the new conditions from the perspective of the academic staff. The research methods included an anonymous online questionnaire of 162 academic staff members from Berdiansk State Pedagogical University and Melitopol State Pedagogical University named after Bohdan Khmelnytsky. The study identified leadership qualities that HEI staff identified as key to stabilizing the institution’s operations in crisis conditions. Responsibility was named by 53.09% of respondents, and strategic thinking by 44.44%. Also, it was found that respondents, in general, positively assessed the results of leadership actions of management in difficult conditions: 29.6% rated them as “very effective” and 54.3% as “effective.” Despite the overall successful adaptation of the studied HEIs, weaknesses in management decisions were revealed, including insufficient emotional support for academic staff and the absence of developed crisis action plans. The study’s conclusions emphasize the importance of further developing professional and moral-volitional qualities of management representatives for effective HEI governance in crisis conditions. The findings may be useful in creating specialized professional development programs for HEI managers in conditions of political, economic, and other instability.